INCLUSION STUDIES ON Î±-CYCLODEXTRIN COMPLEXES OF GLIPIZIDE AND GLICLAZIDE WITH EFFECT OF PH - s, Lizy Roselet; J, Prema Kumari (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To synthesize inclusion complexes of oral antidiabetic drugs, i.e., Glipizide (GP) and Gliclazide (Glc) with a-cyclodextrin (Î±-CD) and varying the pH which will enhance the solubility and thereby oral bioavailability of the drugs. Methods: Liquid inclusion complexes were prepared and characterized by ultraviolet-visible (UV-VIS) spectroscopic studies, and fluorescent studies solid inclusion complexes of GP and Glc with Î±-CD were prepared by co-evaporation method and characterized by differential scanning calorimetric studies (DSC) and1H nuclear magnetic resonance spectroscopic studies (1H NMR). Results: The inclusion complexes of both GP and Glc with Î±-CD showed high binding constant values for pH 2 from the UV-VIS spectroscopy studies and fluorescent studies. DSC and1H NMR spectroscopic studies confirmed the inclusion of GP and Glc inside the Î±-CD cavity. Conclusion: Formed with more stable inclusion complexes, with Î±-CD are GP and Glc at pH 2, along with pH modulation could be a suitable strategy to enhance the solubility and oral bioavailability of both the drugs. Keywords: Solubility, Bioavailability, Glipizide, Gliclazide, Inclusion complexes, Î±-Cyclodextrin. Â